2011
DOI: 10.1038/oby.2010.252
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electrocardiographic Parameters of Altered Repolarization in Uncomplicated Overweight and Obesity

Abstract: IntroductIonAn excessive caloric intake and a low physical activity have as consequence the development of obesity, which, in turn, may lead to an increased risk of cardiovascular morbidity and mortality (1,2). In obese subjects, compared to normal weight subjects, it has been shown a lengthening of corrected QT (QTc) and QT dispersion (QTd) (3,4), parameters related to an increased incidence of ventricular tachyarrhythmias in various pathologies (5-10).Interest has grown, recently, in new electrocardiographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…We were able to extend these observations by showing that VAT was also associated with measures of sympathetic activation on the ECG (HR, QTc, and the ventricular gradient) after adjustment for SAT, while the association of SAT with these measures attenuated after adjustment for VAT. Finally, in line with our results, a recent paper observed an association of BMI with QTc, but not with Tpeak-end (35). We showed the same results for other body fat measures.…”
Section: Tablesupporting
confidence: 82%
“…We were able to extend these observations by showing that VAT was also associated with measures of sympathetic activation on the ECG (HR, QTc, and the ventricular gradient) after adjustment for SAT, while the association of SAT with these measures attenuated after adjustment for VAT. Finally, in line with our results, a recent paper observed an association of BMI with QTc, but not with Tpeak-end (35). We showed the same results for other body fat measures.…”
Section: Tablesupporting
confidence: 82%
“…Moreover, repolarisation markers have been studied in athletes and in non-morbidly obese populations. [26][27][28][29][30] A relationship between Tpe duration and pacing-induced ventricular arrhythmia vulnerability has been demonstrated during electrophysiological study, 31 and data on large cohorts of patients have confirmed its utility as a risk stratification marker for sudden cardiac death and all-cause and cardiovascular mortality. 32,33 It is consequently essential to discriminate between normal and abnormal values in clinical decision-making.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, repolarisation markers have been studied in athletes and in non‐morbidly obese populations …”
Section: Introductionmentioning
confidence: 99%
“…Barbhaiya et al (2013) concluded that both parameters are very useful in assessing the risk of ventricular arrhythmias in patients who underwent resynchronising therapy (Antzelevitch 2008). There are also studies proving the usefulness of these parameters in patients with the Burgada syndrome (Kay et al 1983, Braschi et al 2011. In veterinary medicine, there are isolated reports of the use of these markers and further studies are necessary to confirm their usefulness (Moss 1999).…”
Section: Discussionmentioning
confidence: 99%